Normodajna funkcija organizacij civilne družbe - Igličar, Albin (Pravni letopis, 2011)
The change of the relation between two spheres of social activities, the state one and the one of civil society, is characteristic of the modern time of transformation of global societies into post-modern era. The nature of state is getting more and more the so-called post-modern characteristics, shown mainly in the more and more close connection of the state with civil society. In general there are tendencies to transmit some functions of the state to organizations of civil society. Adoption of general legal acts is going on in an organized way also in some self-managing communities. Already by tradition such a function belongs to local self-government and to religious organizations and scientific corporations (statutes of towns and/or municipalities, general acts of canon law, statutes of universities), and in modern society to various companies and syndicate associations (statutes of joint-stock companies, collective agreements). In this way pluralism of the legal system is being enforced and monopoly of the state in setting general legal norms is diminishing. Organs of self-managing organizations and communities supplement the role of legal institutions.
Keywords: civil society; civilna družba; collective agreement; education; gospodarske družbe; izobraževanje; kolektivne pogodbe; local government; lokalna samouprava; občine; self-managing organizations and communities; statute of joint stock company; statute of municipality; statute of university; statuti